The Effects of Consciousness Raising Grammar Tasks on EFL Students’ Writing Performance: University of Gondar in Focus - Abay, Moges (Ethiopian Renaissance Journal of Social Sciences and the Humanities, 2021)
This study attempted to look into the effects of consciousness raising grammar tasks on EFL learners’ writing performance. The participants of the study were 19 second year students in the department of English Language and Literature, at the University of Gondar, in the 2018/19 academic year. Based on a pragmatic position, quasi-experimental design (time-series design in particular) on a single group of participants was employed. Mixed methods approach was implemented through the application of quantitative and qualitative methods. Thus, these 19 students were taken as one group. Data were gathered through two instruments: writing tests, and diaries. Two writing tests (as pretest1 and pre- test2) were administered before the commencement of the intervention. After the treatment phase, two posttests were administered. That is, posttest 2 was administered two weeks delayed after posttest 1 was administered. Repeated measures t-tests were conducted to determine the significance of the mean difference between the mean results of posttests with that of the pretests. Pearson correlation coefficient was used to describe the relation of the pretests themselves, and the posttests themselves, and to find out the inter-rater reliability. The results have indicated that teaching grammatical points through CRGTs significantly increased learners’ writing performance.